The Effect of Provider Diversity on Racial Health Disparities: Evidence from the Military - Frakes, Michael; Gruber, Jonathan (Review of Economic Studies, 2026)
We assess the relationship between the racial diversity of medical providers and racial health disparities in the use of preventive care and in patient outcomes. We use unique data from the Military Health System, where we observe providers as patients so that we can identify their race, and where moves across bases change exposure to provider race in a plausibly exogenous fashion. We consider patients with four chronic, deadly, but manageable illnesses, where the relationship with the provider may have the most direct impact on health. We find striking evidence that provider racial diversity leads to reduced disparities in maintenance of preventive care and mortality.